Effects of service-learning in foreign and second language courses - Poteau, Christine E. (New York : Routledge, 2020)
"This edited volume brings together several original studies that critically examine the quantitative and qualitative effects of service-learning (SL) on foreign and second learning, and its impact on communities, learners, pre-service teacher candidates, and faculty-researchers. The book focuses on two key aspects: innovative SL methodologies that seek to develop linguistic and cultural competencies and empirical investigations on the SL effects on all stakeholders. The analysis presented provides a unique insight into the challenges and future directions of SL research, pedagogical assessment, and community impact"--
1. Introduction / Christine E. Poteau -- 2. Taking Spanish to the Soup Kitchen: Investigating Students' Foreign Language Anxiety in Service-Learning / Joe Terantino -- 3. Reconsidering Second Language Education through Academic Service-Learning / Jeannette Sánchez-Naranjo -- 4. Community Matters: Reciprocal Service-Learning Program Development for Change / Christine E. Poteau -- 5. Dialogue Journals for Critical Reflection on Community Issues and Academic Writing / Jennifer Shannahan, Betsy Gilliland, and Changho Kwon -- 6. E-Service-Learning: A Case Study of Synchronous Online Language Instruction / Marcella Farina -- 7. In Italia: Learning Language and Culture Assimilation through a Community-Based Experience / Emanuele Occhipinti.
OCLC-licensed vendor bibliographic record.
Keywords: Second language acquisition -- Study and teaching; Service learning; FOREIGN LANGUAGE STUDY / General; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Journalism